EKSPLORASI BAKTERI IDEONELLA SAKAIENSIS SEBAGAI AGEN BIODEGRADASI LIMBAH PLASTIK JENIS PET - Andi Nurfaizah Yusuf; Wirna Arsyad; Yusminah Hala (EDUBIOLOCK, 2025)
Polyethylene terephthalate (PET) is a type of plastic that is difficult to decompose, causing significant environmental impacts. PET biodegradation using microorganisms is a sustainable solution. One of the potential bacteria in this process is Ideonella sakaiensis, which is able to produce the PETase enzyme to decompose PET faster. This study aims to examine the potential of Ideonella sakaiensis in PET biodegradation through the enzymes it produces. The method used is a literature review from various scientific sources regarding the characteristics, degradation mechanisms, and the potential for genetic engineering to increase the efficiency of PET degradation. The results of the study showed that I. sakaiensis was able to accelerate PET degradation 5–120 times faster than natural methods. The potential use of genetic engineering by transforming the PETase gene into Escherichia coli also increases the efficiency of PET plastic degradation.